2003
DOI: 10.1128/aem.69.11.6762-6767.2003
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Lipid Accumulation and Development of Mycelial Structures by Two Arbuscular Mycorrhizal Fungi

Abstract: We monitored the development of intraradical and extraradical mycelia of the arbuscular mycorrhizal (AM) fungi Scutellospora calospora and Glomus intraradices when colonizing Plantago lanceolata. The occurrence of arbuscules (branched hyphal structures) and vesicles (lipid storage organs) was compared with the amounts of signature fatty acids. The fatty acid 16:15 was used as a signature for both AM fungal phospholipids (membrane constituents) and neutral lipids (energy storage) in roots (intraradical mycelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 35 publications
7
85
1
Order By: Relevance
“…We demonstrated that lipid droplets labeled with NR in vesicles decreased within a few days, and colonization resumed between 20 and 50 h after P treatment. The mobility of lipid droplets in vesicles is consistent with previous reports that indicate the inconsistent timing of vesicle formation and accumulation of neutral lipids (Graham et al, 1995;van Aarle and Olsson, 2003;Olsson et al, 2010). McLennan (1926) observed that swelling vesicles are highly protoplasmic and contain many lipids in the mycorrhizal roots of Lolium temulentum (ryegrass).…”
Section: Vesicle Formation Is Induced During P Inhibitionsupporting
confidence: 79%
“…We demonstrated that lipid droplets labeled with NR in vesicles decreased within a few days, and colonization resumed between 20 and 50 h after P treatment. The mobility of lipid droplets in vesicles is consistent with previous reports that indicate the inconsistent timing of vesicle formation and accumulation of neutral lipids (Graham et al, 1995;van Aarle and Olsson, 2003;Olsson et al, 2010). McLennan (1926) observed that swelling vesicles are highly protoplasmic and contain many lipids in the mycorrhizal roots of Lolium temulentum (ryegrass).…”
Section: Vesicle Formation Is Induced During P Inhibitionsupporting
confidence: 79%
“…However, in these experiments with axenic root cultures the authors observed due to feeding of higher Suc amounts an increased carbon transfer from the root to the fungus that was suggested to stimulate P uptake and transfer by the fungus. Here, no indices for a higher carbon transfer from the plant to the AM fungus, deduced from the content of fungus-specific C16:1D 11 and its precursor C16:0 (Trépanier et al, 2005; van Aarle and Olsson, 2005), were found, although levels of available carbon increased. Moreover, the finding of Bü cking and Shachar-Hill (2005) was obtained from experiments with axenic cultures of transformed carrot Figure 5.…”
Section: Discussionmentioning
confidence: 90%
“…We now know that AMF strains differ dramatically in metabolic strategies such as amount of C extracted from their hosts (Jakobsen et al 1992), amount of lipids allocated to storage (van Aarle & Olsson 2003), the transfer of P to their host plants (Boddington & Dodd 1999), C transport capacities across symbiotic interfaces (Dickson et al 1999), and colonization and hyphal-length allocation (Smith et al 2000, Hart & Reader 2005. Fungal allocation strategies can determine benefits conferred to the host.…”
Section: Lozano 2003) There Is No One Single Attribute (Such As N2 Fmentioning
confidence: 99%